Foreign direct investment in India: emerging horizon - Archana, Vani; Basu, P.; Nayak, N.C. (2007)
It has been more than ten years since India embarked on a bold new policy on economic front. In these fourteen odd years there has been progress in both quantity and the way country attracted FDI. There has been a paradigm shift in the flow of FDI and consequent evolution of the country into a low cost, high-tech, R&D intensive behemoth which can not only sustain R&D-intensive industries but also show significant growth in both quality and quantity. This paper intends to study this qualitative shift in the FDI inflow in India in-depth. It reveals that the country is not only cost-effective but also hot destination for R&D activities. Two models appropriate for the study have been made use of. While Panel Data model gives a holistic view, Seemingly Unrelated Regression (SUR) model gives a more detailed view of the changes taking place in the FDI space in India. Results are in conformity with changes taking place at ground level. - Reproduced.
Keywords: Foreign investment